IMPLEMENTASI KEGIATAN KHITOBAH DALAM MENINGKATKAN KEMAMPUAN PUBLIC SPEAKING SANTRI PONDOK PESANTREN ASSYAFI'IYAH PUTRA BUNGAH GRESIK - Muttaqin, Nur Abdillah; Rohmatillah, Nely; Rofiqoh, Nur Indah (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
Public speaking is an essential skill for santrias, the next generation of Islamic preachers. At Pondok Pesantren Assyafi’iyah Putra Bungah Gresik, this skill is enhanced through khitobah activities. This study aims to analyze the implementation of khitobah in improving santri’s speaking abilities, identify supporting and inhibiting factors, and evaluate its effectiveness in building their confidence when speaking in public. This research employs a qualitative method with a case study approach. Data was collected through observations, in-depth interviews with santri, administrators, mentors, and documentation of khitobah activities. The findings indicate that regular khitobah sessions significantly contribute to enhancing santri’s speaking skills. The main supporting factors for this program’s success include motivation from mentors, support from pesantren administrators, rewards for the best-performing santri, and consistency in conducting khitobah activities. However, several challenges remain, such as some santri's lack of confidence in speaking publicly, limited awareness of the importance of this skill, and insufficient experience in addressing an audience. To overcome these obstacles, the pesantren can optimize technology-based training methods, strengthen mentoring systems for less confident santri, and organize speech competitions to boost their competitive spirit. With more effective strategies and continuous improvements, khitobah can become a more optimal instrument in shaping santri who are not only proficient in public speaking but also have a deep understanding of the material they deliver.